Maternal Obesity Enhances Collagen Accumulation and Cross-Linking in Skeletal Muscle of Ovine Offspring - Huang, Yan; Zhao, Jun-Xing; Yan, Xu; Zhu, Mei-Jun; Long, Nathan M.; McCormick, Richard J.; Ford, Stephen P.; Nathanielsz, Peter W.; Du, Min (PLOS ONE, 2012)
Maternal obesity (MO) has harmful effects on both fetal development and subsequent offspring health. We previously demonstrated that MO enhances collagen accumulation in fetal skeletal muscle, but its impact on mature offspring muscle collagen accumulation is unknown. Ewes were fed either a control diet (Con, fed 100% of NRC nutrient recommendations) or obesogenic diet (OB, fed 150% of NRC nutrient recommendations) from 60 days before conception to birth. All ewes received the Con diet during lactation. Male offspring were euthanized at 2.5 years (mean) and the left Longissimus dorsi (LD) muscle and semitendinosus (ST) muscle were sampled. Collagen concentration increased by 37.8±19.0% (P<0.05) in LD and 31.2±16.0% (P<0.05) in ST muscle of OB compared to Con offspring muscle. Mature collagen cross-linking (pyridinoline concentration) was increased for 22.3±7.4% and 36.3±9.9% (P<0.05) in LD and ST muscle of OB group respectively. Expression of lysyl oxidase, lysyl hydroxylase-2b (LH2b) and prolyl 4-hydroxylase (P4HA) was higher in OB LD and ST muscle. In addition, the expression of metalloproteinases (MMPs) was lower but tissue inhibitor of metalloproteinases (TIMPs) was higher in OB offspring muscle, indicating reduced collagen remodeling. MO enhanced collagen content and cross-linking in offspring muscle, which might be partially due to reduced collagen remodeling. Our observation that the collagen content and cross-linking are enhanced in MO offspring muscle is significant, because fibrosis is known to impair muscle functions and is a hallmark of muscle aging.